2023
DOI: 10.1520/jte20220260
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage of Cold Recycled Cement-Treated Mixtures of Asphalt Pavement Materials

Abstract: As with other chemically stabilized materials, cold recycled cement-treated mixtures inherently shrink. Shrinkage cracks might accelerate the rate of pavement deterioration. The research reported here aimed at studying variables that may affect the shrinkage of recycled mixtures. An experimental plan was set to evaluate the effects of cement and reclaimed asphalt pavement (RAP) contents and curing time on the shrinkage of such mixtures with different recycled base course materials (namely cement-treated base [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Other cement that does not react with water would be used as filler to adjust the gradation of CRME [15]. Although studies have shown that cement content did not greatly impact the shrinkage [31,32], it is traditionally believed that excessive cement dosage can lead to material shrinkage and cracking.…”
Section: Cementmentioning
confidence: 99%
See 1 more Smart Citation
“…Other cement that does not react with water would be used as filler to adjust the gradation of CRME [15]. Although studies have shown that cement content did not greatly impact the shrinkage [31,32], it is traditionally believed that excessive cement dosage can lead to material shrinkage and cracking.…”
Section: Cementmentioning
confidence: 99%
“…Although it could spread more stresses under the wheel loading, it would become more like cementstabilized materials and give rise to shrinkage cracking, resulting in reflection cracking on the pavement surface. Although there was research indicating that increasing the cement content would not cause the abovementioned issues [31,32], the specifications still limited the amount of cement used. For instance, in Chinese Technical Specifications for Highway Asphalt Pavement Recycling (JTG/T 5521-2019), it is advisable the cement dosage does not exceed 1.5%, and the amount of cement added in CRME should not exceed 1.8% [40].…”
Section: Ceam and Crmementioning
confidence: 99%
“…With respect to pavement transverse shrinkage cracking, it is more beneficial to simply reverse whether the overall pavement still belongs to the category of linear temperature shrinkage according to the material temperature shrinkage coefficient formula (Formula (2)), and then judge the overall pavement dry shrinkage state as follows [35][36][37].…”
Section: Characteristics Of Temperature Shrinkage Coefficientmentioning
confidence: 99%